Audit committee attributes and firm performance: evidence from Malaysian finance companies - Kallamu, Basiru Salisu; Mohd Saat, Nur Ashikin (Emerald Group Publishing, 2015)
Purpose: The purpose of this paper is to examine the impact of audit committee (AC) attributes on the performance of finance companies in Malaysia in both period before and after the Malaysian Code on Corporate Governance (MCCG) was issued in order to determine which of the AC attributes enhances performance of finance companies in Malaysia. Design/methodology/approach: The population of the study comprises firms listed under finance sector of the main market of Bursa Malaysia. The number of firms listed on the main market of Bursa Malaysia as at the time of data collection (2012) was 822, out of which 37 were finance firms. Since the number of finance companies listed on the main market was only 37, all companies were used as sample for this study. This comprises companies involved in commercial, investment and Islamic banking, insurance, Takaful and other finance-related services. The sample for the period prior to MCCG varies over the period of observation. The number of finance companies in 1992, 1993, 1994, 1995 and 1996 was 36, 40, 44, 47 and 54, respectively. The sample comprises companies in commercial banking, investment banking, Islamic banking, insurance, Takaful and other finance-related services. The sample comprises firms listed on the main board of Kuala Lumpur stock exchange as it was called before the name was changed to Bursa Malaysia. The companies listed under the Ace market are not included due to their small number and because they are subject to different listing requirements. The list of the finance companies for the period 2007-2011 is obtained from the web site of Bursa Malaysia while for the period 1992-1996, the list is obtained from Bursa Malaysia knowledge centre. The observation period for the study covers financial period from 2007 to 2011 which represents post MCCG period while period from 1992 to 1996 represents the period before MCCG. Findings: The findings suggests a significant positive relationship between independent AC members and profitability while dual membership of directors on audit and nomination committee is significant and negatively related with profitability. The result supports agency theory which suggests that independent directors provide effective monitoring of the management thereby enhancing profitability and reducing possibility for opportunistic behavior by the management and ultimately enhancing performance. In addition, the result indicates that there was significant improvement in corporate governance in finance companies after the MCCG was issued compared to the period before it was issued. Research limitations/implications: The study focussed only on finance companies listed on Bursa Malaysia. The attributes examined include independence, expertise, experience, executive membership and interlock of directors, future studies could examine other attributes such as internal process of the committee and personal characteristics of the directors. Furthermore, the study used secondary data future studies could use primary data or a combination of primary and secondary data. The study only examined the period before MCCG and after the code was issued, future study could examine the impact of the first and second revision and compare it with period after the first and second revision. Practical implications: The findings contribute to the literature and the understanding of the influence of AC attributes such as independence and experience of the directors on the committee by showing an association between director independence, expertise, experience and improved performance. Management and board of companies may use the findings to make appropriate choices about AC attributes and governance mechanisms to improve performance particularly with regards to independence, expertise, experience and interlock of the directors. Social implications: The study has provided policy makers with a better understanding of the various features a AC should have which could be incorporated in future policy formulation in order to safeguard investments of shareholders, protect the interest of various stakeholders and enhance the flow of capital and foreign direct investment into finance companies and the economy in general. Comparison of the result between the pre MCCG and post MCCG period shows an improvement in corporate governance in finance companies after the MCCG was issued. This implies that the initial issue of MCCG impacted positively on the governance of the finance companies. Originality/value: To best of the authors knowledge the study is the first to examine the attributes of AC in finance sector as a whole and to examine the impact in the period before and after the MCCG was issued.